Preventing Chronic Pain: A Human Systems Approach—Results from a Massive Open Online Course. Issue 5 (September 2015) - Fricton, James; Anderson, Kathleen; Clavel, Alfred; Fricton, Regina; Hathaway, Kate; Kang, Wenjun; Jaeger, Bernadette; Maixner, William; Pesut, Daniel; Russell, Jon; Weisberg, Mark B.; Whitebird, Robin
Chronic pain conditions are the top reason patients seek care, the most common reason for disability and addiction, and the biggest driver of healthcare costs; their treatment costs more than cancer, heart disease, dementia, and diabetes care. The personal impact in terms of suffering, disability, depression, suicide, and other problems is incalculable. There has been much effort to prevent many medical and dental conditions, but little effort has been directed toward preventing chronic pain. To address this deficit, a massive open online course (MOOC) was developed for students and healthcare professionals. "Preventing Chronic Pain: A Human Systems Approach" was offered by the University of Minnesota through the online platform Coursera. The first offering of this free open course was in the spring of 2014 and had 23 650 participants; 53% were patients or consumers interested in pain. This article describes the course concepts in preventing chronic pain, the analytic data from course participants, and postcourse evaluation forms.